The Influence of Inventory Management on Customer Satisfaction in Retail MSMES - Morgan Nicolas Sitorus; Cahya Adi Achir Kurniyanto; Nurdin Abdul Hamid; Baron Baron; Muhammad Zacky Syauqy Ibnu Shodiq (Journal of Entrepreneurial and Business Diversity, 2025)
Purpose:This study investigates the effect of inventory management on customer satisfaction among retail MSMEs in Tangerang City. Using a quantitative explanatory survey method, the research evaluates the causal relationship between inventory control practices and customer-perceived service outcomes.Methodology:Data were collected through questionnaires administered to 100 customers selected using purposive sampling. Validity, reliability, and normality tests confirmed that the instrument and dataset met statistical requirements. Simple linear regression analysis demonstrated that inventory management has a positive and significant influence on customer satisfaction, indicated by a regression coefficient of 0.564 and a t-count exceeding the critical value. The coefficient of determination revealed that inventory management accounts for 70.3% of the variation in customer satisfaction, while the remainder is influenced by factors outside the scope of this study.Findings:The findings highlight that effective stock monitoring, accurate records, and timely replenishment are key drivers of service quality perceptions, shopping convenience, and repurchase intentions. The study concludes that retail MSMEs must strategically strengthen their inventory systems to improve customer experiences and sustain competitiveness.Implication:Enhancing inventory processes should be viewed not merely as operational control, but as a critical component of customer service performance and business sustainability.